MENINGKATKAN MINAT BACA MELALUI PENGUATAN BUDAYA LITERASI PADA SISWA KELAS III SDN REJOSARI 01 SEMARANG - Selvi Sekartanjung, Kartika; Ngurah Ayu Nyoman Murniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The era of education 4.0 demands an increase in students' interest in reading, especially in elementary schools. Reading culture is key in developing students' knowledge and skills. However, the lack of parental supervision and the influence of technology has caused students' interest in reading to decline. The School Literacy Movement (GLS) at SDN Rejosari 01 aims to increase students' interest in reading. A preliminary study was carried out to identify problems and design research, showing the lack of school facilities and infrastructure to support the literacy movement. However, familiarization and cooperation with the public has been good. The research results show an increase in students' interest in reading through determining favorite books, making their own books, and having a reading room at school. Facilities, infrastructure and public participation are the main focus in increasing student literacy. The era of education 4.0 demands an increase in students' interest in reading, especially in elementary schools. Reading culture is key in developing students' knowledge and skills. However, the lack of parental supervision and the influence of technology has caused students' interest in reading to decline. The School Literacy Movement (GLS) at SDN Rejosari 01 aims to increase students' interest in reading. A preliminary study was carried out to identify problems and design research, showing the lack of school facilities and infrastructure to support the literacy movement. However, familiarization and cooperation with the public has been good. The research results show an increase in students' interest in reading through determining favorite books, making their own books, and having a reading room at school. Facilities, infrastructure and public participation are the main focus in increasing student literacy.